An Efficient Load Balancing Scheme of Energy Gauge Nodes to Maximize the Lifespan of Constraint Oriented Networks - Adil, Muhammad; Khan, Rahim; Almaiah, Mohammed Amin; Binsawad, Muhammad; Ali, Jehad; Saaidah, Adeeb Al; Ta, Qui Thanh Hoai (IEEE Access, 2020)
Resource limited networks have various applications in our daily life. However, a challenging issue associated with these networks is a uniform load balancing strategy to prolong their lifespan. In literature, various schemes try to improve the scalability and reliability of the networks, but majority of these approaches assume homogeneous networks. Moreover, most of the technique uses distance, residual energy and hop count values to balance the energy consumption of participating nodes and prolong the network lifetime. Therefore, an energy efficient load balancing scheme for heterogeneous wireless sensor networks (WSNs) need to be developed. In this article, an energy gauge node (EGN) based communication infrastructure is presented to develop a uniform load balancing strategy for resource-limited networks. EGN measures the residual energy of the participating nodes i.e., $C_{i} \in Network$. Moreover, EGN nodes advertise hop selection information in the network which is used by ordinary nodes to update their routing tables. Likewise, ordinary nodes use this information to uni-cast its collected data to the destination. EGN nodes work on built-in configuration to categorize their neighboring nodes such as powerful, normal and critical energy categories. EGN uses the strength of packet reply (SPR) and round trip time (RTT) values to measure the neighboring node's residual energy ( $E_{r} $ ) and those node(s) which have a maximum $E_{r}$ values are advertised as reliable paths for communication. Furthermore, EGN transmits a route request (RREQ) in the network and receives route reply (RREP) from every node reside in its closed proximity which is used to compute the $E_{r}$ energy values of the neighboring node(s). If $E_{r} $ value of a neighboring node is less than the defined category threshold value then this node is advertised as non-available for communication as a relaying node. The simulation results show that our proposed scheme surpasses the existing schemes in terms of lifespan of individual nodes, throughput, packet loss ratio (PLR), latency, communication costs and computation costs, etc,. Moreover, our proposed scheme prolongs the lifespan of WSNs and as well as an individual node against exiting schemes in the operational environment.
Keywords: Communication cost; Communication infrastructure; Heterogeneous wireless sensor networks; Homogeneous network; Load-balancing schemes; Neighboring nodes; Operational environments; Packet loss ratio; connectivity of wireless nodes; EGN nodes; heterogeneous WSNs; load balancing; low power devices; routing protocol; Wireless sensor network